QSPcc reduces bottlenecks in computational model simulations - Danilo Tomasoni (Nature Portfolio, 2021)
Lombardo and colleagues present QSPcc, a computational code compiler designed to convert code from popular scientific programming languages, such as MATLAB or R, into fast-running C code. This reduces the computational load required for complex modelling approaches and reduces user investment learning additional complex languages.